P115 Subarachnoid haemorrhage with negative initial vascular imaging: a single unit experience. Issue 3 (14th February 2019) - Rasul, F; Silva, G; Fitzpatrick, T; Derakshani, S; Ghosh, A; Vindlacheruvu, R
Abstract : Objectives: To investigate the incidence of vascular abnormality and clinical outcomes in a group of patients presenting with spontaneous subarachnoid haemorrhage (SAH) and negative initial vascular investigation. Design: Single centre prospective cohort study. Subjects: All adult patients with SAH admitted to our unit over a 12 month period. Methods: Prospective collection of data on secure electronic database. Information pertaining to gender, age, mode of initial and subsequent vascular investigations was acquired. Details regarding clinical outcomes at 30 days and complications were documented. Results: 118 consecutive patients with SAH were admitted to our unit over the 12 month study period. 37 patients had negative initial vascular imaging (37/118=31.4%). M:F=19:18, age range 26–76 years. 32 patients underwent a high quality CT angiogram as initial vascular investigation, 5 patients underwent catheter cerebral angiogram (DSA). The most common modality of further vascular imaging was DSA. 5 vascular abnormalities were detected on subsequent vascular imaging (5/37=13.5%). Hydrocephalus and vasospasm were the commonest complications. Clinical outcomes were very good; all patients had a GOS of 5 at 30 days. Conclusions: Patients with SAH and negative initial vascular investigation are an important subset of patients with SAH. There is no uniformity in the type of subsequent vascular investigations selected. Our experience is consistent with previously published studies.